COMPARATIVE EVALUATION OF LEVETIRACETAM AND BRIVARACETAM IN THE MANAGEMENT OF FOCAL EPILEPSY: A PROSPECTIVE OBSERVATIONAL STUDY - LAKSHMI SAI DURGA SIREESHA KANITHI; HIMAJA KUMARI PONNADA; NAKKA ANUSHA VARA PRADA; KALAM SAI SRI; SAYANTHIKA DATTA; SAI SHASHANK GUDLA (Asian Journal of Pharmaceutical and Clinical Research, 2026)
Objective: Focal epilepsy accounts for the majority of epilepsy cases in the global scenario and is often intractable to therapy because of variability in etiology and drug resistance. Levetiracetam (LEV) and its more recently developed analogue brivaracetam (BRV), are widely prescribed antiepileptic drugs acting through synaptic vesicle protein 2A. The present study compares the efficacy, tolerability, and impact on the quality of life of both LEV and BRV in Indian patients with focal epilepsy. Methods: A prospective comparative observational study was done at KIMS Hospitals, Rajahmundry for 6 months. Sixty adult patients were enrolled using purposive sampling and divided into two groups: LEV-Group A and BRV-Group B. Seizure frequency and health-related quality of life by World Health Organization Quality of Life-BREF were assessed at baseline, 3 months, and 6 months. The statistical tools used included paired and independent t-tests. Results with p<0.05 were considered significant. Results: Both LEV and BRV were associated with a significant reduction in seizure frequency, with p<0.001. BRV was associated with a numerically greater mean reduction of 2.56 versus 2.17, though this did not reach statistical significance. Quality-of-life improvement was noted in both groups, though higher gains were realized in the BRV group in various areas: Physical and psychological. In both, the reported adverse effects were of a mild nature, though behavioral disturbances were more frequent with LEV. Conclusion: LEV and BRV are equal in efficacy with regard to seizure control, but BRV shows better tolerability and a slightly greater improvement in quality of life, supporting its role as a preferred alternative for patients who are intolerant to LEV.